The role of digital technologies in the development of everyday oral vocabulary in a foreign language for hearing-impaired children - Сайдаева, Баян; Намазбаева, Жамиля; Аутаева, Акбота (Pedagogy and Psychology, 2022)
The article discusses the role of digital technologies in the development of everyday vocabulary in a foreign language for hearing-impaired children. In this article, a study was made of the theoretical and practical relevance, effectiveness and significance of digital technologies in learning for students, parents and teachers. Theoretically, the works of domestic and foreign scientists were analyzed. Based on the results of the analysis, a practical survey was conducted among the population, in particular, undergraduates, students, doctoral students and students in various fields, and a good result was obtained. He showed that digital technologies are still relevant not only for hearing-impaired schoolchildren, but also for ordinary schoolchildren and teachers. And it is obvious that the ways of solving this relevance are diverse.